Building common defects on coastal reclamation area in Johor / Alia Quraisah Mohd Esa - Mohd Esa, Alia Quraisah (Faculty of Architecture, Planning and Surveying, 2010)
Johor is the state of Malaysia that just being developing to increase the quality of life for the local people. For this reason, there are many ideas and development planning to increase the erection quality in Johor for population purpose. There are many new land opened for those purpose. Land reclamation becomes the alternative methods by government to enlarge the coastal area. From many research, there are many problems arise toward buildings on reclamation area. The coastal area contributes to defects by nature factors at coastal area such as salty air, solar radiation, rough wind and rain, and some more. The reclamation also contributes to the defects of cracks from settlement or movement by the consolidation process. The objective of the studying of common defects at coastal area is to identify types, to categorize, and to analyzes the mostly of common defects, occur in building at coastal reclamation area in Johor. The methodology to obtain the objectives of study is from the condition survey (checklist), interview, and responds from questionnaire. The data then converted into the form of graph and table using suitable calculation method. The finding from the analysis of the condition survey had come out with the types of defects occur at coastal area. The data collected also categorised by structure, nonstructure, and services from elements of the buildings. The questionnaire also analyzed in form of chart using mean index method. Basically, the defects occur to the building at coastal area is similar to the other common building’s defects. The difference is the coastal area receives more radiation from sunlight directly and the salty air containing in the atmosphere due to the location nearby the sea quicken the deterioration.